Hubungan Resiko Ergonomi dengan Kejadian Musculosceletal Disorder pada Pengguna Laboratorium Teknologi Pertanian Universitas X - Sisca Mayang Phuspa (Indonesian Journal for Health Sciences, 2017)
Activities in the lab include the practice, research, and experimentation have its health risks (ergonomic disorder) unconciously.This Research was conducted on 56 respondents (including students, lecturer and laboratory) at the Agricultural Technology Laboratory of University X at April 2016. This study used surveys and observations by weighting and scoring methods for risk analysis and statistical tests to determine the relationship between the level of risk with Ergonomic events Disorder (Musculoskeletal Disorders) using coefficient of contingency. Determination of respondents using total sampling methods. The results showed that 55.4% of the study population activities in laboratories have high risk and moderate 44.6% for others. On the other variables, it’s known to have 43% of the study population experienced ergonomic disorder symptoms and 57% did not. The results of statistical analysis showed a relationship with a correlation coefficient of 0.26. The conclusion of this study is that the unergonomical behavior caused ergonomic disorder in the laboratory of Agricultural Technology, University X and it is caused by the lack of laboratory facilities and lack of socialization of safety and health laboratory.